Selective Hyaluronan–CD44 Signaling Promotes miRNA-21 Expression and Interacts with Vitamin D Function during Cutaneous Squamous Cell Carcinomas Progression Following UV Irradiation - Bourguignon, Lilly Y. W.; Bikle, Daniel (Frontiers in Immunology, 2015)
Hyaluronan (HA), the major extracellular matrix component, is often anchored to CD44 isoforms, a family of structurally/functionally important cell surface receptors. Our recent results indicate that UV irradiation (UVR)-induced cutaneous squamous cell carcinomas (SCC) overexpress a variety of CD44 variant isoforms (CD44v), with different CD44v isoforms appear to confer malignant SCC properties. UVR also stimulates HA degradation in epidermal keratinocytes. Both large HA polymers and their UVR-induced catabolic products (small HA) selectively activate CD44 isoform-mediated cellular signaling in normal keratinocytes and SCC cells, with all of the downstream processes being mediated by RhoGTPases (e.g., RhoA and Rac1). Importantly, we found that the hormonally active form of vitamin D (1,25(OH)2D3) not only prevents the UVR-induced small HA activation of abnormal keratinocyte behavior and SCC progression, but also enhances large HA stimulation of normal keratinocyte activities and epidermal function(s). Furthermore, we found that HA and its UVR-induced catabolic products (e.g., large and small HA) selectively activate CD44-mediated Rac and RhoA signaling. Specifically, large HA-CD44 interaction promotes Rac/PKNγ-dependent normal keratinocyte differentiation, DNA repair and keratinocyte survival. Conversely, small HA-CD44v isoform interaction stimulates RhoA/ROK-dependent NFκB signaling and microRNA-21 (miR-21) production, leading to inflammation, proliferation (following acute UVR response) and SCC progression (following chronic UVR exposure). Active vitamin D inhibits small HA-CD44v-mediated RhoA/ROK signaling and SCC progression; and it also enhances large HA-CD44-mediated differentiation, DNA repair and normal epidermal function. Selective applications of large HA and vitamin D will be used to improve the UVR-induced HA (small vs. large HA)-CD44 isoform interaction with RhoGTPase signaling and skin inflammation as a potential therapeutic treatment for skin cancer.